Expression of miRNAs (146a and 155) in human peri-implant tissue affected by peri-implantitis: a case control study - Munir Nasr Hamed; Hayder Raad Abdulbaqi (BMC, 2024)
Abstract Background In literature, the levels of miRNA-146a and miRNA-155 are increased in periodontitis. Limited data are available regarding the expression of miRNA-146a and miR-NA-155 in diseased human peri-implant tissue. Therefore, the objective of this study was to explore the expression of miRNA-146a and miRNA-155 in human gingival peri-implant tissue affected by peri-implantitis. Methods After recording the clinical parameters, human peri-implant pocket tissues were harvested from sites diagnosed with peri-implantitis (n = 15 cases) in addition to healthy peri-implant sulcus tissues (n = 15 controls). The levels of miRNA-146a and miRNA-155 were assessed using real-time qPCR. Results Cases exhibited a significantly higher mean expression of miRNA-155 (5.2-fold increase) and miRNA-146a (2.8-fold increase) than controls. MiRNA-155 and miRNA-146a demonstrated an appropriate sensitivity (87.5% and 87.5%, respectively) and specificity (73.3% and 66.7%, respectively) in discriminating cases from controls. A moderate correlation (r = 0.544, p = 0.029) was found between miRNA-155 and miRNA-146a levels in the case group. Conclusions The expressions of miRNA-146a and miR-NA-155 are different between healthy and peri-implantitis affected tissues. Both miRNAs might potentially able to discriminate healthy from peri-implantitis affected tissues.